Dysregulated Exosomes Result in Suppression of the Immune Response of Pregnant COVID-19 Convalescent Women - Cao, Hang; Abd Aziz, Nor Haslinda; Xavier, Janet Raja; Shafiee, Mohamad Nasir; Kalok, Aida; Jee, Babban; Salker, Madhuri S.; Singh, Yogesh (Frontiers in Molecular Biosciences, 2022)
A successful pregnancy outcome is dependent on a delicate balance between inflammatory and anti-inflammatory processes throughout the different trimesters. Interruption in this balance can lead to an adverse outcome resulting in pregnancy loss. Since late 2019, the emergence of the new SARS-CoV-2 virus affected lives worldwide including pregnant women, therefore, there is an urgent need to address different approaches in relation to prevention, diagnostics and therapeutics. Early pregnancy is affected by SARS-CoV-2 infection leading to fetal demise. Available evidence also suggests that 90% of pregnant women infected with SARS-CoV-2 virus seem to be asymptomatic. Nonetheless, it is still unclear how pregnant women recovered from COVID-19 affect the exosomes production and, how these exosomes regulate the adaptive immune response. In this study, we found that several exosomes including CD9, CD31, CD40, CD45, CD41b, CD42a, CD62P, CD69, CD81, CD105 and HLA-DRDPDQ in the plasma of recovered COVID-19 pregnant women were significantly less abundant compared with a control group. Further, to understand how these exosomes affect the adaptive immune response, we co-cultured the peripheral blood mononuclear cells (PBMCs) from healthy control (HC) pregnant women with the exosomes of either Preg-HC or Preg-recovered COVID-19 women. We identified that Preg-recovered COVID-19 women have reduced capacity for the inflammatory cytokine TNF-a from cytotoxic CD8+ T cells. In sum, our study highlights that pregnant recovered COVID-19 women have reduced production of several exosomes and possess less immunogenic properties. Our study implicates that exosomes can control inflammation and antigen presentation capacity of immune cells thus, limiting the infection.